2014
DOI: 10.1111/1742-6723.12174
|View full text |Cite
|
Sign up to set email alerts
|

Implications for public access defibrillation placement by non‐traumatic out‐of‐hospital cardiac arrest occurrence in Singapore

Abstract: In this study, we found the categories and individual sites that clearly fulfilled the American Heart Association criteria of at least 1 OHCA per site per 5 years. This study provides a model of how cardiac arrest registry data can be used to guide local health policy on automated external defibrillator deployment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…was selected after full-reading. After full-text reading,17 papers were included [10][11][12]3,13,14,4,15,5,[16][17][18][19][20][21][22][23] . Agreement between the two reviewers was good (kappa 0.90).…”
Section: Resultsmentioning
confidence: 99%
“…was selected after full-reading. After full-text reading,17 papers were included [10][11][12]3,13,14,4,15,5,[16][17][18][19][20][21][22][23] . Agreement between the two reviewers was good (kappa 0.90).…”
Section: Resultsmentioning
confidence: 99%
“…(11) Over the years, some private and public organisations installed AEDs in various locations, but as there was no national AED registry prior to 2013, the public and the SCDF 995 control room were unaware of the existence of these AEDs. (12) Due to the absence of servicing contracts, maintenance of the AEDs was performed by the individual organisations, who, due to the low utility, may not be aware of the need for regular battery and pad replacement. In 2014, the MHA started the first AED leasing contract for public access AEDs under the Save-A-Life scheme, which bundled the cost of maintenance with that of replacement batteries and pads.…”
Section: Need For An Aed Registrymentioning
confidence: 99%
“…Kitamura et al noted a relationship among increasing density of AED coverage, improved response times and survival. (44) A local study (45) found that port/airport/immigration checkpoints, hotels/ hostels, transport facilities, sports/recreational facilities, and health/medical care facilities are high-yield public sites for AED placement. A registry for AED integration, R-AEDi, has recently been established to help link fi rst responders to the nearest AED during an emergency.…”
Section: Ensuring Effectiveness Of Pad Programmementioning
confidence: 99%